Letramento, gênero e raça na trajetória acadêmica de uma indígena mulher Akwe - Borges, Suety Líbia Alves (2022)
In this research, I investigate how the identities of an Akwẽ indigenous woman are being (re)constructed in her academic trajectory, with a view to problematizing issues of literacy, gender and race. The inverse is also analyzed, how the identity markers – gender and race – impact their path, with regard to literacy practices presupposed by this academic context, the master's degree, and by the master's student herself. The data were generated within the literacy workshops held by me, voluntarily, as support for the development of the participant's academic activities, remotely, through the Google Meet platform. Among other points, this is one that makes the study innovative. The teaching methodology used in the workshops was built on the path, due to the need to carry it out, at a distance, in view of the social isolation caused by the COVID-19 pandemic. It is important to say that this is a work that is part of the advisor's larger research project – Nascimento (2018-2022) – entitled "Academic literacies in contact zones: trajectories of indigenous students in graduate programs", and, therefore, based on the ethical, methodological and epistemological commitments that guide him towards a scientific practice based on indigenous paradigms and intercultural perspectives. In this way, this doctoral research brings important subsidies to (re)think public policies, in addition to teaching practices, that can guarantee the permanence of indigenous people in postgraduate programs. Another important point is the study's contribution to the expansion of the concept of literacy which, in addition to being situated in social, cultural and power relations, in the thesis, is also situated in systemic relations, based on the systemic laws presented by Bert Hellinger (2006; 2020), which are: Order, Belonging and Balance.